From Separate and Unequal to Integrated and Equal? School Desegregation and School Finance in Louisiana - Reber, Sarah J. (The Review of Economics and Statistics, 2011)
School desegregation might have induced unintended behavioral responses of white families as well as state and local governments. This paper examines these responses and is the first to study the effects of desegregation on the finances of school districts. Desegregation induced white flight from blacker to whiter public school districts and to private schools, but the local property tax base and local revenue were not adversely affected. The state legislature directed significant new funding to districts where whites were particularly affected by desegregation. Desegregation therefore appears to have achieved its intended goal of improving resources available in schools that blacks attended.